2022
DOI: 10.3390/ani12030297
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Nano Plastic in the Aquatic Environment: Methodological Problems and Challenges

Abstract: Microplastic research has become a buzz word. It is seen as one of the most pressing issues of Anthropocene contamination. There is certainly no doubt about the ubiquitous presence of microplastic (MP) in almost all environmental matrices. However, the validity of considering them as a vector for contaminants needs some reconsideration, there are other more potent pathways. Their effect on marine biota also calls for some realistic experiments with environmental concentrations of MP and nanoplastic (NP). It ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 237 publications
0
17
0
Order By: Relevance
“…On the other hand, we would also like to question the relevance of the generated information regarding polymers, when the health risk assessments are not using the polymer type but the size, hence suggesting that just assuming that the particle detected is plastic is sufficient? [31].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, we would also like to question the relevance of the generated information regarding polymers, when the health risk assessments are not using the polymer type but the size, hence suggesting that just assuming that the particle detected is plastic is sufficient? [31].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The presence of microplastics in the air has been related to release from clothing, furnishings, synthetic tires, and degraded plastics, among other causes [1][2][3]6,17,[29][30][31][32][33][34]. Aerosols can be a significant pathway for transferring MPs to humans via inhalation [4,23,[35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-fragmented plastic particles are very tiny in size, which means that, after reaching the aquatic environment, they are likely to be mistaken easily as food or as prey by the higher trophic organisms from the food webs, such as fishes; in fact, the majority of the plastics ingested by fishes are found in the form of small particles [ 15 ]. Several studies have suggested that, apart from wastewater, surface runoffs, various industrial and hospital effluents and agricultural runoffs, the aeolian transportation and precipitation can also play a key role in accumulating primary and secondary plastic particles into the aquatic environments [ 2 , 8 , 16 , 17 , 18 ].…”
Section: What Is a Plastic Particle?mentioning
confidence: 99%
“…In fact, plastics are present in all aquatic compartments including surface water, water column, and sediments, and a significant amount of these are small plastic particles (≤5 mm); thisform of plastics can stay in the environment for a long time [ 8 ]. Moreover, the COVID-19 pandemic is likely to act as catalyst for short- and long-term impacts on freshwater ecosystems withthe emergence of face masks, gloves, gowns and other plastic appliances as environmental litter, makingmicroplastic pollution in freshwaters more severe [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%